Implementation of Ecological Literacy in the Context of Implementing Character Education in the Independent Curriculum - Efendi, Rika; Aunurrahman, Aunurrahman; Erlina, Erlina (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research aims to analyze the implementation of ecological literacy for the implementation character education in the independent curriculum. In writing this research, the author used a qualitative approach to obtain relevant data and data sources. A qualitative design was implemented and carried out on class teachers and class 4 students. The subject of this research writing was the character values possessed by class 4 students at SD Negeri 09 East Pontianak. Data collection techniques use interviews and document analysis. The data analysis technique used is an interactive model whose elements include data reduction, data presentation, and drawing data conclusions. Thus the results of this research show that the importance of Ecological literacy for the Implementation of Character Education in the Independent Curriculum is very relevant in the process of instilling character values in students. Through the formation of love for the environment in forming character, students are able to appreciate and practice and interpret ecological literacy in students' daily lives both in the school, family and community environments. The implications of this research are that it is hoped that teachers will be able to use ecological literacy projections as an illustration of the process of instilling character values in learning both in preparing, implementing the learning process and developing curriculum in schools paying attention to students' needs and potential so that the results obtained have an impact on children's concern for the environment with character.